Debt-growth nexus in the MENA region: Evidence from a panel threshold analysis - Mohammed Daher Alshammary; Zulkefly Abdul Karim; Norlin Khalid; Riayati Ahmad (Economies, 2020)
This study examines whether a debt-to-GDP threshold exists in the public debt and economic growth relationship for 20 Middle East and North Africa (MENA) countries from 1990 to 2016 using the threshold estimation technique. The empirical results reveal that there is a threshold effect in the public debt and economic growth relationship. The MENA region's debt-to-GDP threshold value as a developing region is lower than the debt threshold computed by earlier studies for developing countries. We found that the effect of public debt on economic growth is significant and positive only below the threshold value of debt-to-GDP. More precisely, debt has a promoting influence on economic growth when the debt is less than 58% of the GDP. This finding indicates that the relationship between public debt and economic growth is contingent on the debt-to-GDP ratio. Importantly, policymakers need to be more prudent when establishing a policy regarding debt issues.
Keywords: E62; H63; N17; C24; 330; economic growth; MENA region; public debt; threshold effects